An elastic-induced buckling column with enhanced dissipation capacity for vibration suppression of jacket platforms. (15th February 2023) - Ji, Shubin; Wang, Cong; Meng, XiangJian; Wei, Yingjie
Abstract: Wave impacts on jacket platforms cause severe vibrations and slow decay in steel structures with low damping, which results in plastic damage and fatigue failure. To simultaneously resist impact and attenuate vibration, an EIB (elastic-inducing buckling) column exhibiting high stiffness and enhanced dissipation capacity is achieved via combining a pre-compressed spring and an asymmetric column proposed in the authors' previous work. Analytical models for the EIB column are derived and mutually verified with FEA (finite element analysis), and parameter studies are conducted to provide design guidance based on the validated analytical models. Results indicate that the EIB column substantially increases the dissipated energy (more than fourfold) compared with the asymmetric column. For engineering applications, via the FE model combined with the UMAT (user-defined material) code in ABAQUS, the dynamic responses of a representative jacket platform assembled with the EIB column exhibit rapid decay behaviors. This work demonstrates the potential of the EIB column for achieving simultaneously high stiffness and enhanced damping in marine structures.